INTENCIONALUMO STRUKTŪRA IR GENEZĖ HUSSERLIO FENOMENOLOGIJOJE. - Jonkus, Dalius (Problems / Problemos, 2008)
The article discusses the concept of intentionality in Husserl's phenomenology. The task of investigation is to show that static structure of intentionality can have prolongation in the genetic concept of intentionality. The concept of intentionality cannot be reduced to theoretical relation with object of cognition. Intentionality is practical realization, transitive movement and teleological process. Intentionality is a process of transition from one act to another. Phenomenological analysis cannot limit itself to only one separate act since every separate act posses the potential transition to another act, while every separate act preserves the interconnection with the integral intentional life. Phenomenology reject concept of nonintentional consciousness, because nonintentional acts of consciousness cannot be described like phenomena. From the other side Husserl affirm that not every act of consciousness can to reach a last goal. With other words, every act of consciousness implicate not only requirement for a plenitude of fulfillment, but in the same time implicate unconscious or unrealizable experience.